Risk factors for intraoperative in-stent thrombosis during stent-assisted coiling of paraclinoid aneurysms - Zeng, Chun; Wang, Jing (Frontiers in Neurology, 2024)
Objectives: To identify independent risk factors for intraoperative in-stent thrombosis (IST) in paraclinoid aneurysms (PAs). Methods: 172 PA patents undergoing stent-assisted coiling (SAC) were divided into an IST group (n = 12) and a non-IST group (n = 160). Clinical characteristics, aneurysm morphologies, and laboratory parameters were measured. We performed independent t tests (for normally distributed data) or non-parametric tests (for non-normally distributed data) to compare continuous parameters. Multivariate logistic regression analysis with a stepwise forward method was conducted to determine independent risk factors. Receiver operating characteristic curves were generated, and the Delong test was employed for comparisons. Results: Independent risk factors for IST included size ratio (SR) (p < 0.001, odds ratio [OR] = 3.909, confidence interval [CI] = 1.925–7.939), adenosine diphosphate (ADP) inhibition (p = 0.028, OR = 0.967, CI = 0.938–0.996), and reaction time (R) (p = 0.006, OR = 0.326, CI = 0.147–0.725). The combined factors (SR, ADP inhibition, and R) exhibited area under the curves of 0.870, 0.720, 0.716, and 0.697, with cutoff values of 2.46, 69.90%, and 4.65, respectively. Conclusion: The SR, ADP inhibition, and R values were independent risk factors for the IST in the PAs undergoing SAC. For PAs with a large SR, surgeons could prepare for long-term dual antiplatelet therapy before SAC.